Edubot Project: From the Classroom to the Job Market - Maciel, Beatriz de Siqueira; Silva, Lukas Araujo Da; Passos, Jamile Sardinha; Silva, Jwlyah de Sousa; Baptista, Roberto de Souza (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This study addresses the relationship between robotics education in high school and students’ interest in pursuing careers in the technology field. The objective of this study is to comprehend how the use of educational robotics may better prepare students for both the classroom and the labor market. Through a qualitative approach using interviews, the study examined the impact of the Edubot project on students’ social interaction, knowledge sharing, and team organization skills. The findings provide valuable insights to reinforce the significance of robotics education in the school curriculum and enhance students’ skill development for successful integration into the job market.